Early Detection of Autism Spectrum Disorder: Comparison between Screen- and Non-Screen Regions - Elín Ástrós Þórarinsdóttir 1992- (2020)
Given the rising prevalence rate and burden associated with autism, early detection and intervention are more important now than ever before. There is a growing interest in adding autism-specific screening as a complement to routine developmental surveillance in order to facilitate early detection and intervention; however, this has been a subject of debate. The purpose of the current study was to evaluate the outcome of implementing population-based autism screening at the 30-month-visit within the well-child care in Iceland. Three regions were compared: an experimental region in the capital area, in which children received autism-specific screening with the Modified Checklist for Autism in Toddlers, Revised with Follow-Up (M-CHAT-R/F) in addition to routine developmental surveillance, and two comparison regions (one in the capital area and one outside the capital area) in which children received only routine developmental surveillance. The target population were all children scheduled for their 30-month visit to the well-child care in Iceland from March 2016 through October 2017 (N = 7173). Participants were all children who were diagnosed with autism after their 30-month well-child visit and until 31. October 2019 in each of the three study regions (N = 119). Our results indicate that population-based autism-specific screening does advance early identification and intervention for autism, but only for children who screen positive. When only those children who participated in screening and screened positive on the M-CHAT-R/F in the experimental region were included in statistical analyses (excluding both non-screened children and false negatives), the screen-positives were referred for diagnostic evaluation at a significantly and meaningfully younger age than children in both comparison regions. Our results underscore the importance of further studies on population-based autism screening for young children, and the need to continue the quest for effective screening instruments that are able to identify autism ...